Oral ridaforolimus plus trastuzumab for patients with HER2+ trastuzumab-refractory metastatic breast cancer - Seiler, Milton; Ray-Coquard, Isabelle; Melichar, Bohuslav; Yardley, Denise A; Wang, Rui X; Dodion, Pierre F; Lee, Mark A (Clinical breast cancer, 2015)
BACKGROUND: Although trastuzumab-containing therapies prolong survival in patients with metastatic breast cancer (MBC), most tumors develop trastuzumab resistance, potentially mediated by aberrant phosphatidylinositide 3-kinase (PI3K)/AKT signaling. Ridaforolimus (a mammalian target of rapamycin [mTOR] inhibitor) may overcome trastuzumab resistance by inhibiting PI3K signaling. METHODS: A single-arm, phase IIb trial was conducted to evaluate the efficacy and safety of ridaforolimus-trastuzumab in human epidermal growth factor receptor 2-positive (HER2(+)) trastuzumab-refractory MBC (NCT00736970). Ridaforolimus was administered orally (40 mg daily) for 5 d/wk plus weekly trastuzumab. The primary end point was objective response (OR). RESULTS: Thirty-four patients were enrolled (91% had received 1 or 2 previous trastuzumab-based therapies, whereas 9% had received 3 previous therapies). The most common reasons for discontinuation were disease progression (62%) and adverse events (AEs; 24%). Three patients died; 1 because of bowel perforation, which was possibly ridaforolimus related. Partial response was observed in 5 patients (15%). Median duration of response was 19.1 weeks (range, 15.9-80.1 weeks). Fourteen patients (41%) achieved stable disease (SD); 7 patients (21%) maintained SD for ≥ 24 weeks. The clinical benefit response (CBR) rate was 34.3%. Median progression-free survival (PFS) and overall survival (OS) were 5.4 months (range, 0-20.3 months; 95% confidence interval [CI], 2.0-7.4) and 17.7 months (range, 0-25.9 months; 95% CI, 8.8-20.8), respectively. PFS rate at 6 months was 37%. The most common treatment-related AEs were stomatitis (59%), diarrhea (27%), and rash (27%). CONCLUSION: Ridaforolimus-trastuzumab was well tolerated and demonstrated antitumor activity in trastuzumab-resistant HER2(+) MBC.
Keywords: senioři; metastázy nádorů; analýza přežití; Carcinoma, Ductal, Breast; Breast Neoplasms; Receptor, ErbB-2; senioři nad 80 let; trastuzumab; Survival Analysis; receptor erbB-2; Middle Aged; aplikace orální; Adult; Sirolimus; sirolimus; Breast cancer; chemorezistence; Aged, 80 and over; duktální karcinom prsu; Neoplasm Metastasis; ženské pohlaví; Humans; Drug Resistance, Neoplasm; HER2; Antibodies, Monoclonal, Humanized; humanizované monoklonální protilátky; Ridaforolimus; lidé středního věku; Administration, Oral; Antineoplastic Combined Chemotherapy Protocols; nádory prsu; protokoly protinádorové kombinované chemoterapie; Trastuzumab; dospělí; Female; Aged; mTOR inhibitor; lidé